Tituli ante cocturam sur deux tegulae de Montenach (Moselle) et Thorame-Haute (Alpes-de-Haute-Provence) : nouvelle édition et apports à la question de l’organisation du travail dans les tuileries gallo-romaines - Claudia Gatta (Gallia)
Roman bricks and tiles were often inscribed with marks and inscriptions of all kinds for a wide variety of ‘professional’ and ‘occasional’ purposes. This paper focuses on two ‘professional’ inscriptions on tiles from Montenach (Moselle) and Thorame-Haute (Alpes-de-Haute-Provence). A detailed re-reading of the new edition of these two tituli highlights their original features compared to other known ante cocturam inscriptions. In addition, these documents provide an insight into the writing practices, work organization and know-how of the manufacturers employed in the Gallo-Roman brickyards. The social and legal aspects are also examined.